ANALISA RASIO KEUANGAN DALAM MENENTUKAN KEPUTUSAN INVESTASI - Rita Rita; I Gusti Ayu Diah Dhyanasaridewi (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
The capital market has an important role in the economy and people's welfare to support life in the future, because the capital market has two functions at once, namely the economic function and the financial function. The economic function is a function that provides a facility that is found between investors and parties who need funds. The financial function also plays a role as an imbalance that is obtained by the owner of the fund for the investment capital he has. This study discusses the influence of ROE, PBV, and PER in determining investment decisions at PT. Gudang Garam Tbk, PT. H.M Sampoerna Tbk, PT. Indonesian Tobacco Tbk, and PT. Bentoel Internasional Investama Tbk. This type of research is classified as quantitative research using secondary data. The population in this study are companies engaged in the cigarette industry which are listed on the Indonesia Stock Exchange as many as 4 companies using a system of financial ratios and fundamental analysis